Basic Analysis of Foreign Exchange Cost Allocation at PT X Using Activity Based Costing Method - Khansa Fatin; Nureni Wijayati (Quantitative Economics and Management Studies, 2023)
This article is a case study on a multinational company that has the risk of exchange rate differences arising from foreign currency translations as a result of business transactions using foreign currencies. The difference in foreign exchange costs that arise needs to be allocated up to the product level so that the unit of analysis can calculate the appropriate production costs to produce product profitability accurately and reliably. The approach used in this study is a descriptive analysis research using qualitative methods. The results of the research will find the right allocation base to be used as the basis for the allocation of foreign exchange costs at PT X and see the impact on the profitability of the business unit in the analysis unit so that it can help the analysis unit make reliable decisions.